15 GANCICLOVIR IN CONGENITAL CYTOMEGALOVIRUS INFECTION ASSOCIATED WITH PULMONARY HYPERTENSION. (1st January 2005) - Malik, S.; Daroka, P. J.; Silio, M.
Abstract : Background: Symptomatic congenital CMV infections are associated with significant complications with mortality rates as high as 12%, frequently with evidence of organ involvement in the reticuloendothelial, CNS and hepatobiliary systems. Congenital CMV with severe pulmonary hypertension is rarely reported in the literature and the optimum treatment in this scenario is unknown. Case Report: A 3 month old female, born to a 22 years old primigravida at 34+ weeks, was admitted with vomiting, diarrhea, dehydration and respiratory distress requiring intubation. Mother's prenatal evaluation was significant for CMV infection diagnosed after amniotic fluid was obtained at 24-26 weeks of pregnancy. Postnatal course was significant for thrombocytopenia, intermittent respiratory distress, FTT, hepatosplenomegaly, elevated transaminases, recurrent diarrhea and vomiting, and pulmonary hypertension diagnosed 3 weeks prior to admission. At birth, urine CMV culture and urine for inclusions were negative. However, because of the clinical findings and prenatal evaluation, diagnosis of congenital CMV was made. Patient received blood transfusion postnatally and was sent home on O2 by nasal canula. On admission, echocardiogram revealed severe pulmonary hypertension. Patient received fluid boluses, 100% oxygen, milrinone, sodium bicarbonate and nitrous oxide. CMV antigenemia revealed 252 positive cells/150, 000. Ganciclovir at a dose of 5 mg/kg/qo 12 hours was started on day 4. Open lung biopsy on day 6 revealed grade I vascular changes of pulmonary hypertension, cellular interstitial pneumonitis, chronic peribronchiolitis and adventitial chronic perivasculitis with focal localization of CMV antigen in airspaces and in the media and adventitia of muscular pulmonary arteries on immunohistochemistry stains. IV ganciclovir was given for 6 weeks with improvement in respiratory status and 50 days after hospitalization, CMV antigenemia had decreased to 6 cells/150, 000. Conclusions: Congenital CMV infections can be associated with pulmonary hypertension and ganciclovir may be considered for severely symptomatic infants. Larger studies are needed to evaluate the association of pulmonary hypertension with congenital CMV, as well as the appropriate therapy for symptomatic infants.